Divergent Synthetic Strategy To Access the Polyketide Subunits of Aurilides: Synthesis of the Southern Fragment of Lagunamides D and D′ - Michon, Synthia; Garcia, Maxime; Cavelier, Florine; Salom-Roig, Xavier J. (Synthesis, 2025)
We report a flexible stereocontrolled synthetic route to the southern fragment of lagunamides D and D′, two cytotoxic cyclodepsipeptides of the aurilide family. Key steps in the route include an anti-aldol Abiko–Masamune reaction and a Horner–Wadsworth–Emmons (HWE) olefination. The key element of our synthetic strategy was the use of a pivotal intermediate which allows the introduction a side chain that differentiates the polyketide structure of the members of the family. Thus, to illustrate the synthetic potential of our strategy, we have also prepared four different advanced polyketide precursors.
Keywords: cytotoxicity; macrocycles; aldol reaction; chiral auxiliaries; asymmetric synthesis